RETRACTED: MiR-1236-3p Inhibits the Proliferation, Invasion, and Migration of Colon Cancer Cells and Hinders Epithelial-Mesenchymal Transition by Targeting DCLK3 - Zhao, Yibin; Zhou, Hongyi; Shen, Jie; Yang, Shaohui; Deng, Ke; Li, Qi; Cui, Wei (Frontiers in Oncology, 2021)
Background Dysregulated microRNAs (miRNAs) are common in human cancer and are involved in the proliferation, promotion, and metastasis of tumor cells. Therefore, this study aimed to evaluate the expression and biological function of miR-1236-3p in colon cancer. Methods This study screened the miRNA in normal and colon cancer tissues through array analysis. In addition, quantitative Reverse Transcription–Polymerase Chain Reaction (qRT-PCR) analysis was performed to validate the expression of miR-1236-3p in normal and tumor tissues from colon cancer patients and cancer cell lines. Online predicting algorithms and luciferase reporter assays were also employed to confirm Doublecortin Like Kinase 3 (DCLK3) was the target for miR-1236-3p. Moreover, the impact of miR-1236-3p on the progression of colon cancer was evaluated in vitro and in vivo. Western blotting and qRT-PCR were also performed to investigate the interactions between miR-1236-3p and DCLK3. Results MiR-1236-3p was significantly downregulated in colon cancer tissues and its expression was associated with the TNM stage and metastasis of colon. In addition, the in vitro and in vivo experiments showed that miR-1236-3p significantly promoted cancer cell apoptosis and inhibited the proliferation, invasion, and migration of cancer cells. The results also showed that miR-1236-3p hindered Epithelial–mesenchymal Transition (EMT) by targeting DCLK3. Moreover, the expression of DCLK3 mediated the effects of miR-1236-3p on the progression of cancer. Conclusions MiR-1236-3p functions as a tumor suppressor in colon cancer by targeting DCLK3 and is therefore a promising therapeutic target for colon cancer.